2019
DOI: 10.3390/molecules24101918
|View full text |Cite
|
Sign up to set email alerts
|

All You Need to Know about the Kinetics of Thermally Stimulated Reactions Occurring on Cooling

Abstract: In this tutorial overview article the authors share their original experience in studying the kinetics of thermally stimulated reactions under the conditions of continuous cooling. It is stressed that the kinetics measured on heating is similar to that measured on cooling only for single-step reactions. For multi-step reactions the respective kinetics can differ dramatically. The application of an isoconversional method to thermogravimetry (TGA) or differential scanning calorimetry (DSC) data allows one to rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In particular, = 0.5 was predicted by collision theory in the homogeneous gas phase and = 1 was predicted by transition state theory. Other modifications of the Arrhenius equation, including the stretched exponential, super- and sub-Arrhenius models [ 21 , 30 , 31 ], can also be easily used within the proposed approach.…”
Section: Results Of Theoretical Analysis— Proposed Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, = 0.5 was predicted by collision theory in the homogeneous gas phase and = 1 was predicted by transition state theory. Other modifications of the Arrhenius equation, including the stretched exponential, super- and sub-Arrhenius models [ 21 , 30 , 31 ], can also be easily used within the proposed approach.…”
Section: Results Of Theoretical Analysis— Proposed Approachmentioning
confidence: 99%
“…The classical Arrhenius equation is widely used for calculations in both methods, which may be considered as a disadvantage, since a number of studies have shown that its various modifications significantly improve the accuracy of determining the kinetic parameters [ 20 , 21 ]. In particular, Criado et al [ 20 ] examined the dependence of the preexponential factor on temperature and estimated the errors involved in the activation energy calculated from isothermal and non-isothermal methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The postulated decrease in the rate constant of cellular reactions that is theorized to occur with reduction of temperature may lead to better corneal donor preservation. 8 Even a one-hour delay in cooling results in lower glucose levels in the stroma and aqueous, harming endothelial integrity. 14 , 15 For corneal transplant surgery, the viability of the endothelium is largely predictive of successful transplants and some studies have assessed whether hypothermia can act to preserve the endothelium, with many either finding no correlation or a correlation only with a longer DTP time (>12hr).…”
Section: Discussionmentioning
confidence: 99%
“…4 The premise behind hypothermic storage of tissue stems from the concept that the rate constant of cellular reactions is exponentially proportional to temperature. 8 Therefore, at a reduced temperature, cells decrease their metabolism and oxygen consumption, preventing mitochondrial stress and hypoxia-induced apoptosis. Most corneal transplants depend largely on preservation of a viable endothelium.…”
Section: Introductionmentioning
confidence: 99%